Establishment and evaluation of an in vitro blast lung injury model using alveolar epithelial cells - Chunjie Ding; Shan Hong; Miao Zhang; Yunzhe Sun; Ning Li; Jing Zhang; Lan Ma; Linqiang Tian; Wenjie Ren; Lin Zhang; Sanqiao Yao (Frontiers Media S.A., 2022)
BackgroundGas explosion is a fatal disaster commonly occurred in coal mining and often causes systematic physical injuries, of which blast lung injury is the primary one and has not yet been fully investigated due to the absence of disease models. To facilitate studies of this field, we constructed an in vitro blast lung injury model using alveolar epithelial cells.MethodsWe randomly divided the alveolar epithelial cells into the control group and blast wave group, cells in the blast wave group were stimulated with different strengths of blast wave, and cells in the control group received sham intervention. Based on the standards we set up for a successful blast injury model, the optimal modeling conditions were studied on different frequencies of blast wave, modeling volume, cell incubation duration, and cell density. The changes of cell viability, apoptosis, intracellular oxidative stress, and inflammation were measured.ResultsWe found that cell viability decreased by approximately 50% at 6 h after exposing to 8 bar energy of blast wave, then increased with the extension of culture time and reached to (74.33 ± 9.44) % at 12 h. By applying 1000 ~ 2500 times of shock wave to 1 ~ 5 × 105 cells /ml, the changes of cell viability could well meet the modeling criteria. In parallel, the content of reactive oxide species (ROS), malonaldehyde (MDA), interleukin 18 (IL-18), tumor necrosis factor alpha (TNF-α), and transforming growth factor beta (TGF-β) increased in the blast wave group, while superoxide dismutase (SOD) and Glutathione -S- transferase (GST) decreased, which were highly consistent with that of human beings with gas explosion-induced pulmonary injury.ConclusionAn in vitro blast lung injury model is set up using a blast wave physiotherapy under 8 bar, 10 Hz blast wave on (1 ~ 5) ×105 alveolar epithelial cells for 1 000 times. This model is flexible, safe, and stable, and can be used for studies of lung injury caused by gas explosion and blast-associated other external forces.